Spatial urban restructuring for economic growth with distribution: The case of Ceara (Brazil) - Raphael Bar-El; Dafna Schwartz (European Regional Science Association (ERSA), 2003)
One of the most important challenges of economic policy is the combination between economic growth and the reduction of inequality and poverty. The change of the regime in Brazil can be seen as a reaction to the failure of economic policy in this field. We focus on the case of one of Brazil's states in the Northeast, Ceara, that experienced a rapid macro economic growth in the last decade, but with no reduction of poverty and inequality. Established economic theory shows that economic growth generally implies a changing economic structure (relatively less agriculture, and more industry and later services), and a process of urbanization. Our hypothesis is that in addition to industrialization and urbanization, a component of spatial urban restructuring is necessary for the achievement of a more equalitarian economic growth. The persistence of inequalities and high levels of poverty in spite of the macro economic growth can be explained by the continuing high level of urban concentration, and the insufficient growth of urban centers outside the metropolis. We test this using data of economic growth in Ceara, compared with trends of urbanization and its concentration level, changing economic structures (distribution between agriculture, industry and services) in the regions outside the metropolis and levels of productivity. Results lead to the conclusion that economic policy measures should consider a spatial reallocation of public expenditures for physical and human infrastructures, leading to a spatial urban restructuring.
Keywords: 330